Ruthenian Devotional Songs As Collectors’ Items? - Stern, Dieter (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
At the turn of the sixteenth and the seventeenth centuries, syllabic devotional songs in Ruthenian (RDS) make their first appearance as occasional appendices or notes in the margins of manuscripts serving quite divergent functions (triodia, evangelia and the like). The first systematic collections of RDS were compiled abroad by Ruthenian monks having left Ukraine for monasteries around Moscow from the 1660s onwards. It required several more decades, till the beginning of the eighteenth century, before these songs were also being systematically collected in song manuscripts throughout the Ruthenian lands themselves. The article argues against established views to the effect that this documentary gap was due to a massive loss of seventeenth-century Ruthenian song manuscripts. It should rather be taken at face value as an indication that some perceptual change with respect to devotional songs is likely to have taken place among Ruthenian literate classes at the beginning of the eighteenth century. It is argued that the rise of Ruthenian song manuscripts marks the beginning of a collecting culture, which treats devotional songs as a cherished and coveted collectable, where heretofore no particular value seems to have been accorded to these songs. The article explores the social profiles of song collectors and the individual makeup of song collections to offer a hypothetical outline of this emerging collecting culture, addressing issues of modes of exchange, methods of collecting and compiling, the specific relationship between collector and collectable, with a view to arguing for a highly individualized and intimate culture between private devotion and incipient object-oriented consumerism.